Romantic Pendulum in Our Literature - Supriyanto, Teguh (Balai Bahasa Jawa Tengah, 2017)
The aim of this research is to find out and to describe (1) is the romantic ideology dominant in the works of the non- tradition of Balai Pustaka, (2) works of 1970-period, and (3) works of 2000 period. These questions arisen based on the real fact that the romantic ideology influenced the series of the history of Indonesian Literature, further more before modern Indonesian literature arisen, since 9-14 century in the old Javanese. This ideology is also find out in 19 century and in the works of Balai Pustaka tradition in 1920-1945.The data were taken by using random sampling. The structural-semiotics method and dialected method used to analize the data. The results of this research: (1) the works non Bapalai Pustaka tradition mainly in 1920 is dominated of realism ideology. (2) in popular literature (1970) is found out that romantics ideology is pseudo romanticism. The works in 1970, mainly the popular literature is as if as romanticism although pseudo-romanticism. Recently, the romantic ideology is played, distorted, re-bulit by using a ?pseudo-romaticism? word.